Porta coeli: the Annunciation as Threshold of Salvation - Dell’Acqua, Francesca (Convivium, 2015)
Abstract In one of his earliest monographs, Hans Belting recognized the painted crypt of the Abbot Epyphanius (824-842) in the monastery of San Vincenzo al Volturno as the most important cycle in early medieval South Italy. Belting developed an interpretation of the murals, their style, and content, by tracing connections over a wide geographical perspective. Though challenged over the years and eventually generally rejected, his reading of the crypt remains thought provoking. A response to the questions involved, this paper focuses on a specific image in the crypt, the Annunciation visible on the sides of the fenestella confessionis. This faded mural is one of the earliest Annunciations extant in which the protagonists are flanking an opening, as became conventional later in the Middle Ages. The appearance of this kind of Annunciation is considered here by reconstructing the east-west circulation of theological concepts during the Iconoclastic controversy; by identifying the textual imagery derived from these concepts; and by analyzing the translation from textual to visual as a result of influencing the religious mentality.